Figurative Language Translation Techniques Used in Jhumpa Lahiri's Short Stories - Iosephine Sere Gratia; Yules Orlando Sianipar (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
Translation is an essential element that is the most appropriate and efficient solution to accelerate scientific and technological progress in developing countries. Translation is the key for people all over the world to be able to share data, stories, experiences, and especially information. However, translation is a complex skill. High precision is needed to be able to translate the source language (SL) into the target language (TL) correctly to convey the true meaning. In this research, we analyze the translation techniques used to translate the types of figurative language used in short stories. We used a descriptive qualitative method and manual qualitative data analysis. This research is limited to two short stories of Interpreter of Maladies and Penerjemah Luka which is Sexy and Seksi, alongside This Blessed House and Rumah yang Diberkati. As a result, there are 62 data obtained. We categorized the types of figurative language found in the two short stories using translation techniques from Molina and Albir. We found that some types of figurative language were not used by the author and some translation techniques were not used by the translator to convey the figurative language successfully.